(untitled) (Journal of history, 2018)
The purpose of the work is to identify some issues of ethnic identity in traditional Kazakh culture in Turkey The task of scientific work is to reflect, compare and describe some ethnic identities of Kazakhs residing in the territory under consideration, their living conditions, their way of life, profession, traditional culture. The methodology of the study is based on an analSis of the problems of ethnic identity and the concepts of a primitive-oriented approach that allow a comprehensive and sStematic review of the problem. Based on the conclusions of the concept of primordialism, we are considering the question of the preservation and features of traditional culture based on the ethnic identity of our compatriots in Turkey, based on the conclusion that the identification of a specific ethnos is given in the genetic code. The study is based on general scientific history, consistency, comparative and experimental analSis. Based on the historical-comparative method, the ethnic identity of the Kazakhs in Turkey is considered. The factors influencing the change in the way of life of our fellow citizens in Turkey are determined. Key words: Turkish Kazakhs, ethnic identity, problems of resettlement, primary, features in the professions.